ANALISIS PERBANDINGAN PERCEPATAN PERCEPATAN PADA PROYEK JALAN DENGAN ALTERNATIF CRASHING PENAMBAHAN JAM KERJA DAN TENAGA KERJA - Dafa Athalla Nabhan Saikhu; I Nyoman Dita Pahang Putra (Racic : Rab Construction Research, 2025)
The road project in Lumajang Regency is one of the projects that experienced delays in work caused by several factors. One of them is uncertain weather such as continuous rain that affected sometask cannot be carried out on time or cannot be continued which had an impact on other work. The solution that can be used to accelerate project completion time is to carry out a comparative analysis of acceleration of implementation time on projects using the crashing method using alternatives to increase working hours and the number of workers to obtain maximum completion time for work that is on the critical path. In the crashing method, can generate the Crash Duration, Crash Cost, and Cost Slope analysis is carried out on work activities that are crashed. After that, the most efficient results of accelerating the duration of the project were obtained, namely by alternatively adding working hours which could speed up the project completion time by 25 days from the normal completion time of 219 days and a total cost of 9.465.138.216,75. Hitting the alternative of adding working hours can exceed the project completion target of the initial project plan duration.